Biochemical, Hematological and Clinical Profile of Dengue Patients in a Tertiary Care Centre - Ramsha Waseem; Hania Tariq; Abdul Rafey; Zain Nasir; Momina Hayat; Javed Iqbal (Proceedings, 2025)
Background: Dengue is an arboviral infection caused by four dengue virus serotypes (DENV 1–4), with a global incidence that disproportionately affects tropical and subtropical regions. Despite a significant disease burden in Pakistan, local data on the hematological and biochemical profiles of different dengue categories is limited and not generating reliable evidence for clinical decision making.